PEMANFAATAN HERBAL DALAM PENYEMBUHAN LUKA BAKAR - Betania, Putri (Journal of Pharmacy Tiara Bunda, 2021)
Burns are damage to skin tissue caused by contact with sources that conduct heat. Burns can cause impaired appearance, function, patient dependence, job loss and future survival. Handling and proper treatment will avoid things that are not desirable such as infection in burns. Use the medical treatment continuous sometimes has adverse side effects, so that treatment using traditional plants is an alternative treatment. This literature study aims to determine the potential of traditional plants that can be used for healing burns obtained from published research journals. Aloe vera (L.) Burm. F., Allium ascalonicum L., Artocarpus altilis, Pandanus amaryllifolius Roxb and Piper betle Linn. are some plants that have the potential to help heal burns. The content of secondary metabolite compounds contained in it can help in healing burns such as flavonoids, alkaloids, tannins and saponins